Effect of Five Types Inert Dust to Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae) in Stored Rice Seeds - Astuti, Ludji Pantja; Maula, Rohmatin; Rizali, Akhmad; Mario, Muhammad Bayu (The Journal of Experimental Life Science, 2019)
Rhyzopertha dominica (F.) is one of the primary pests in stored rice. Generally, pest control in the storage was done by spraying and fumigation using synthetic insecticide. The application of chemical insecticide using phosphine can cause resistant to insect pests and toxic to humans. Regarding the negative effect of insecticide application, the alternative control by using natural resources like inert dust is expected to be a good solution to control pests of stored products. This research was aimed to study the effectiveness of five inert dusts, which are: rice husks ash, volcanic ash, giant bamboo leaves ash, corncobs ash, coconut shells ash to adult mortality and the inhibition of population growth of R. dominica on stored rice seeds. The results showed that giant bamboo leaves at 8 g kg-1 caused 100% of mortality and faster than other inert dusts tested. Giant bamboo leaves and rice husks were more effective to suppress the number of eggs, larvae, pupae, and new adults (F1). Inert dust could decrease the hatchability of eggs, inhibit population growth, and decrease the weight of new adults (F1). The damage to the treated rice seeds was significantly lower than untreated rice seeds. Keywords: ash, control, inert dust, silica, stored product pest